CHARACTERIZATION OF NANOPARTICLES PRODUCED BY CHLOROFORM FRACTION OF KAEMPFERIA ROTUNDA RHIZOME LOADED WITH ALGINIC ACID AND CHITOSAN AND ITS BIOLOGICAL ACTIVITY TEST - Atun, Sri; Arianingrum, Retno (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main objectives of this research are to characterize of nanoparticles produced by chloroform fraction of K. rotunda loaded with alginic acid and combination alginic acid-chitosan, and its biological activity test.Â Methods: Chloroform fraction of K. rotunda was loaded on alginic acid and combination of alginic acid-chitosan nanoparticles by ionic gelation method in various compositions. Characterizations of the products were investigated in particle size, zeta potential, and morphology by Scanning Electron Microscopy (SEM). The biological activity of the products as an antioxidant was tested by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The cytotoxic effect was analysed using MTT [3-(4,5 dimethyltiazol-2-yl)-2,5-diphenyltetrazoilium bromide] assay. Result:The nanoparticles alginic acid can be synthesized at the optimal mass ratio range of alginic acid : CaCl2 of 10 :1 (% w/v),the percentage nanoparticle products was100%, Â the size range of the nanoparticles were 87 to 584 nm, with a zeta potential of -39.0 mV, Â and the morphology shows a spherical shape and smooth surface. Furthermore, nanoparticles result from the combination of alginic acid-chitosan at the optimal mass ratio range of alginic acid : chitosan of 10 :1 (% w/v) and added calsium ion at 0.015% w/v, the percentage nanoparticle products was100%, the size range of the nanoparticle were 87 to 877 nm, with a zeta potential of -27.1 mV, and Â the morphology shows a form of rectangular beam. Conclusion: The nanoparticle products of chloroform fraction of K. rotunda loaded alginic acid and combination alginic acid-chitosan were successfully obtainedÂ by ionic gelation method. The nanoparticle products show lower activity in antioxidant and cytotoxic effect against human breast cancer T47D cell lines than the starting material chloroform fraction of K. rotunda. Â